Tannic Acid-Steeped Corn Grain Modulates in vitro Ruminal Fermentation Pattern and Microbial Metabolic Pathways - Zhao, F. F.; Zhang, X. Z.; Zhang, Y.; Elmhadi, Mawda; Qin, Y. Y.; Sun, H.; Zhang, H.; Wang, M. Z.; Wang, H. R. (Frontiers in Veterinary Science, 2021)
This study investigated the effects of tannic acid (TA) treated corn on changes in ruminal fermentation characteristics and the composition of the ruminal bacterial community in vitro. Ruminal fluid was obtained from 3 rumen-fistulated goats fed a 60:40 (forage:concentrate) diet. The batch cultures consisted of 25 mL of strained rumen fluid in 25 mL of an anaerobic buffer containing 0.56 g of corn grain (corn steeped in water (Con), 15 g/kg TA solution (TA15), 25 g/kg TA solution (TA25), 35 g/kg TA solution (TA35) for 12 h), 0.24 g of soybean meal, 0.10 g of alfalfa and 0.10 g of oat grass. After incubation for 24 h, TA treated corn caused to raise (P < 0.05) ruminal pH and the molar proportion of acetate, reduce (P < 0.05) total volatile fatty acids and the molar proportion of butyrate compared with the Con treatment. Illumina MiSeq sequencing was used to investigate the profile changes of the ruminal microbes. A principal coordinate’s analysis plot based on weighted UniFrac values revealed that the structure of the ruminal bacterial communities in the control group was different from that of the TA-treated corn groups. The results of changes in the rumen bacterial communities showed that TA treated corn enriched (P < 0.05) Rikenellaceae_RC9_gut_group, but reduced (P < 0.05) Ruminococcaceae_NK4A214_group, Ruminococcus_2 and unclassified_o__Clostridiales. Functional prediction of ruminal microbiota revealed that the TA-treated corn weakened ruminal microbiota function of utilizing starch through pyruvate metabolism. In conclusion, TA-treated corn can modulate the rumen fermentation characteristics, microbial composition and metabolic pathways, which may be potentially useful for preventing the occurrence of ruminal acidosis.